Depressurization-induced gas production from hydrate reservoirs in the Shenhu sea area using horizontal well: Numerical simulation on horizontal well section deployment for gas production enhancement - Wan, Tinghui; Li, Zhanzhao; Yu, Yanjiang; Liang, Qianyong; Lu, Hongfeng; Wang, Jingli (Frontiers in Earth Science, 2023)
In 2020, China successfully conducted the second round of natural gas hydrate pilot production with horizontal wells at W11-W17 deposits in the Shenhu sea area of South China Sea, but the average daily gas production is far from reaching the commercial exploitation. Low productivity has become one of the key factors hindering the commercial exploitation of gas hydrate reservoir. This work taking SHSC-4 well as an example, uses numerical simulation method to analyze the impact of the placement of horizontal well section, length and the production system on productivity of horizontal well in depressurization exploitation. From the analysis of simulation results, it can be seen that the best performance of production capacity can be achieved when horizontal section placed in layer II, which is compared with that placed in layer I and III. More importantly, hydrate in layer I and free gas in layer III can be effectively utilized to improve productivity when layer II is exploited. When the horizontal section is arranged in layer II and produced by depressurization with small pressure difference (1MPa), the longer the horizontal section length is, the better the productivity will be. However, the average cumulative gas production increment per meter is gradually decreasing. According to the simulation results, 300m is a reasonable horizontal section length for the exploitation of layer II, and the cumulative gas production reaches 2.55 million cubic meters after 60 days of continuous exploitation. In addition, due to the limitations of convective heat transfer in the low-permeability reservoir in the Shenhu sea area, sensible heat can significantly improve the secondary hydrate generated in the wellbore and the reservoir around the wellbore due to throttling expansion effect, which has a good effect on productivity improvement. Compared with the situation without heating, when the horizontal section is arranged in layer II and the length is 300m, the production mode of depressurization and combined heating is adopted, and the cumulative gas production of 60 days with different pressure difference (1MPa~5MPa) is 0.14, 5.55, 14.75, 23.72 and 29.5 times higher than that without heating.